The Anticancer Activity of the Marine Sponge Aaptos suberitoides to Protein Profile of Fibrosarcoma Mice (Mus musculus) - Noor Nailis Sa'adah; Awik Puji Dyah Nurhayati; Maya Shovitri (IPTEK The Journal for Technology and Science, 2016)
The study was aimed to evaluating anticancer activity of A. suberitoides on protein profile of blood plasma of fibrosarcoma mice (M. musculus). Mice were induced by Benzo(a)pyrene on the subcutaneous tissue intravenously with a concentration of 0,3 gram/0,2 oleum olivarum/day for 2 weeks. Mice were treated with ethanolic extract of A. suberitoides every day for two weeks. There were six groups. The first group (I) was control. Group II, mice were induced by CMCNa, Group III mice were treated by Cyclophosphamide. Group IV, V and VI mice were treated by ethanolic extract of A. suberitoides with 500, 1000 and 1500 mg/weight. Mice blood were taken at week fifteen. Protein profile of mice was measured by electrophoresis SDS-PAGE. The protein profile indicated that the mice were induced benzo(a)pyrene (Group II, III, IV, V and VI) have a new protein band (41 kDa). The protein band not presented in control (Group I). The protein band ( 7 kDa) was in Groups I and II, but it not presented in Groups III, IV, V and VI. The most interesting protein band was 115 kDa, which presented only in Groups II, III and IV. The research showed that the sponge extract with concentration of 1000 and 1500 mg/weight repressed the expression of protein 115 kDa